Analisis Kemampuan Disposisi Matematis Siswa MAN 1 Sintang Melalui Pendekatan Metaphorical Thinking - Ananda, Devia; Afifah, Fajar Nur; Sopia, Nurapni (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2022)
This research is motivated by the importance of the ability of mathematical disposition to the material of arithmetic sequences and series in terms of mathematical ability. Where the purpose of learning mathematics contains cognitive aspects seen from problem solving abilities and affective aspects can be seen from mathematical dispositions.This study aims to describe the ability of mathematical disposition for the material of arithmetic sequences and series in terms of the aspect of mathematical ability.The place of implementation in this research is at MAN 1 Sintang with class XI research subjects. The approach used in this study uses a qualitative approach.Data retrieval is carried out by giving a problem-solving ability test question, giving a mathematical disposition questionnaire,and conducted interviews based on the results of the problem-solving ability test questions by each subject. The conclusion from the results of this study is that the students' mathematical dispositions are generally in good criteria